Člen 147 OZ v sodni praksi v primeru novinarjev in urednikov - Mežnar, Špela (Pravni letopis, 2015)
The position of the Slovenian Supreme Court, according to which staff journalists and editors (employees) are not subject to the privilege of exclusive liability of their employer (media company) for damage caused by ordinary negligence, is neither justified nor theoretically correct. This applies to both arguments, applied by the highest court: first, it is not true that the intent to write an article per se contains the intent to cause damage. Second, Article 6 (and Article 18) of the Media Act do not constitute a lex specialis (as an exception) in relation to 147 Code of Obligation. In the case law of the higher courts differing views can be found. While Ljubljana High Court rejects the Media Act as a legal basis justifying deviation from Article 147 Code of Obligation both for editors and journalists alike, Maribor High Court believes that only Article 18 Media Act represents the legal basis for the direct responsibility of the editors as the journalists' work is "less responsible" and therefore not subject to direct liability. The author believes that there is no need to treat staff journalists and editors more harshly than other employees in Slovenian civil law. Journalistic and editorial work is certainly responsible, but not more than some other professions in which the liability of the employer for their staff in case of negligent behavior has never been disputed % doctors, judges or teachers. The author further believes that this trend is problematic both in terms of the regulations regarding the responsibility of the employer towards the worker, as well as in terms of the constitutional provisions on freedom of expression and the principle of equality.
Keywords: delodajalci; novinarji; obligacijsko pravo; odškodninska odgovornost; uredniki; zaposleni